Famous Five : Five Go Adventuring Again - Enid Blyton (London, United Kingdom Hachette Children's Group, 2001)
There's a thief at Kirrin Cottage! The Famous Five think they know who it is, but they need to prove it! Where can they find evidence? The discovery of an old map and very unusual hiding place is all they need to get to the bottom of this mystery and uncover the true culprit!
Keywords: Mystery -- Mystery